BAHAN AJAR BAHASA ARAB MENGGUNAKAN SMARTPHONE PADA SEKOLAH MENENGAH PERTAMA - Muhammad Fahrurrozi; Safarwadi , Safarwadi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
Arabic is a foreign language that is inseparable from the lives of Indonesian society, which is predominantly Muslim.For Muslims, it is recommended to understand Arabic as a basis for understanding and making it easier to understand the Koran. Currently Arabic has been implemented in several places.Madrasah at the Senior High School level, students are prepared to achieve basic language competency, which includes four language skills that are taught integrally, namely listening, speaking, reading, and writing. Learning Arabic can be said to be successful if students have mastered four language skills both verbally and in writing. Because the results of this research aim to help and make it easier for students to learn Arabic with the help of applications in the form of Arabic teaching materials. This application testing is reviewed based on several criteria, namely the appearance of the application, the content of the application material, and the benefits of the application to users. The user satisfaction level of the application is 76% for teachers and 75% for students.